math

posted by Samantha

When the problem says "Angel transformed the following equation from 6x+4-×=2 (×+1) to
10=2 (×+1). He then stated that the solution to the equation is ×=4. Is he correct? Explain"
when I solved the equation I got 24=10 and 10=10. However, im having trouble explaining it... please help!

  1. Damon

    scroll down

Respond to this Question

First Name

Your Answer

Similar Questions

  1. algbera

    In solving the equation (x + 3)(x + 1) = 48, Eric stated that the solution would be x + 3 = 48 => x = 45 or (x + 1) = 48 => x = 47 However, at least one of these solutions fails to work when substituted back into the original …
  2. math

    In solving the equation (x + 4)(x – 7) = -18, Eric stated that the solution would be x + 4 = -18 => x = -22 or (x – 7) = -18 => x = -11 However, at least one of these solutions fails to work when substituted back into the …
  3. algebra

    solving the equation (x+4)(x-4)=9 Eric stated that the solution would be x+4=9>x=5 or (x-4)=9=>x=13 However one of these solution fails to work when subsituted back to the original equation. Why?
  4. algebra

    1. In solving the equation (x + 3)(x + 1) = 48, Eric stated that the solution would be x + 3 = 48 => x = 45 or (x + 1) = 48 => x = 47 However, at least one of these solutions fails to work when substituted back into the original …
  5. intermediate algebra

    In solving the equation (x-1)(x+2)=30. Eric stated that the solution would be x-1=30¨T¡úx=31 or(x-2)¨T30¨T¡úx=32 However, at least on of these solutions fails to work when subsitituted back into the orignal equation. Why is …
  6. Math

    I don't understand how to solve this problem: In solving the equation (x + 3)(x + 1) = 48, Eric stated that the solution would be x + 3 = 48 => x = 45or (x + 1) = 48 => x = 47 However, at least one of these solutions fails to …
  7. Algebra

    In solving the equation (x + 3)(x + 1) = 48, Eric stated that the solution would be x + 3 = 48 => x = 45 or (x + 1) = 48 => x = 47 However, at least one of these solutions fails to work when substituted back into the original …
  8. intermediate algebra

    in solving the equation (x+4)(x-4)=9 eric stated the solution would be x+4=9 =>5 or x-4=9 =>13 however at least one of these solutions fails to work when subsituted back into the original equation. why is that?
  9. algebra

    in solving the equation (x +2)(x - 2) = 32 eric stated the solution to be x + 2 = 32 => x = 30 or x- 2 = 32 => x = 34. however at least one of these solutions fails to work when plugged back into the equation. why is that?
  10. math

    When the problem says "Angel transformed the following equation from 6x+4-×=2 (×+1) to 10=2 (×+1). He then stated that the solution to the equation is ×=4. Is he correct?

More Similar Questions